The Promotion/Inhibition of the Seepage Transport of Copper Ions by Suspension-Colloidal Particles with Wide Size Gradation. (30th May 2021) - Nie, Qingke; Li, Huawei; Yang, Haipeng; Ni, Tengfei; Jiang, Sichen
Abstract : Sand column tests were conducted to investigate the seepage transport of silicon powders (SPs) with two wide particle size ranges (30-2000 nm and 2-70  μ m), including the cotransport of SPs and copper ions. The results show that the graded large-scale SP has an obvious inhibiting influence on the transport of copper ions. In contrast, in the presence of the graded small-scale SP, the concentration of copper ions in the effluent tends to increase; i.e., there appears to be a promoting effect. However, after a long transport distance, the presence of SPs, regardless of particle size, has an overall retarding effect on heavy metal pollutants (e.g., copper ions). The promoting effect of the increase in seepage velocity on the concentration of copper ions in the effluent is greater with the graded large-scale SPs than with the graded small-scale SPs. In terms of the microstructural characteristics by metallographic microscopy, the average particle size of the deposited graded small-scale SPs is almost constant at different transport distances, while that of the deposited graded large-scale SPs tend to decrease significantly with increasing transport distance; i.e., notable bed filtration is exhibited in the latter case. This physical mechanism also determines the sequence and rate of the retarding effect of SPs on heavy metal ions under seepage flow.